Perkembangan Kognitif Anak Usia Dini - A. Rajamuddin, Ida Maiyanti (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Early childhood cognitive development is a crucial process influenced by both internal and external factors, including learning stimulation, parental involvement, and contextual educational approaches. This study emphasizes the effectiveness of scientific, thematic, and play-based learning methods in enhancing logical thinking, creativity, and problem-solving skills in children aged 4–6 years. Parents play a vital role as primary educators by providing appropriate educational support at home. Theoretical frameworks from Jean Piaget and Lev Vygotsky explain the stages of cognitive development and the importance of social interaction. Genetic, environmental, experiential, maturational, and technological factors also contribute significantly to a child’s cognitive growth. Practical methods such as experiments, mind mapping, multisensory approaches, and project-based learning have been proven effective in fostering children’s critical thinking and conceptual understanding. A supportive learning environment at home and school is essential in laying a strong foundation for children’s future academic and social success.